2014
DOI: 10.2478/10004-1254-65-2014-2408
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sperm morphology in mouse germ cells after short-term exposures to acetamiprid, propineb, and their mixture

Abstract: Pesticides are one of the most potent environmental contaminants, which accumulate in biotic and abiotic components of ecosystems. Acetamiprid (Acm), a neonicotinoid insecticide, and Propineb (Pro), a dithiocarbamate fungicide, are widely used to control sucking insects and fungal infections on crops, respectively. The present study was undertaken to investigate the genotoxic effects of these compounds, individually and in mixtures, in mouse germ cells by using the sperm morphology assay. Mice were injected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…It has been demonstrated that acetamiprid caused to change in serum testosterone levels and seminiferous tubule diameter and thickness in albino mice exposed to 0.16 mg/ml, and 0.22 mg/ml, by adding acetamiprid to drinking water for four weeks 16 . According to a study which was conducted by Rasgele 17 , acetamiprid did not increase the sperm abnormalities at the doses of 0.62, 1.25, and 2.50 μg/mL after 24 and 48 hours on in Mus musculus mice. A study conducted by Kong et al 18 demonstrated that acetamiprid increases LH levels and decreases testosterone levels and sperm count in Sprague Dawley rat treated with 10 mg/kg and 30 mg/kg dose.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that acetamiprid caused to change in serum testosterone levels and seminiferous tubule diameter and thickness in albino mice exposed to 0.16 mg/ml, and 0.22 mg/ml, by adding acetamiprid to drinking water for four weeks 16 . According to a study which was conducted by Rasgele 17 , acetamiprid did not increase the sperm abnormalities at the doses of 0.62, 1.25, and 2.50 μg/mL after 24 and 48 hours on in Mus musculus mice. A study conducted by Kong et al 18 demonstrated that acetamiprid increases LH levels and decreases testosterone levels and sperm count in Sprague Dawley rat treated with 10 mg/kg and 30 mg/kg dose.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, serum testosterone concentration and sperm quality and quantity were affected [17]. In the study of mouse sperm abnormalities following intraperitoneal administration of acetamiprid and propineb together as well, acetamiprid did not significantly increase the percentage of abnormal sperm after 24 or 48 h exposure [12].…”
Section: Discussionmentioning
confidence: 94%
“…There are several reports on chemically induced abnormal sperms. [75] reported the sperm abnormalities in mouse germ cells after short term exposure to pesticides acetamiprid, propineb and their mixture. From various studies it has been concluded that chemicals yielding positive response in mouse sperm morphology test should be regarded as suspected germ cell mutagens in mammals and agent’s positive responses in these sperm tests should be considered with high priority against human applications [110] , [111] .…”
Section: Introductionmentioning
confidence: 99%